Customer Experiences in the B2B software industry – The collaborative nature of value creation and customer experiences - Kivinummi, Ville (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
While the conceptual foundations of customer experience have long been present, the more holistic concept of customer experience is a relatively recent development. Increasing competition fueled by the globalized marketplace requires organizations to seek new means of differentiation and competitive advantage, which led to the emphasis on providing superior customer experiences to supplement their offerings and services, accentuating the importance of experiential aspects of doing business. The purpose of the study is to identify and outline the factors contributing to the customer experience in the B2B software industry. The purpose is supplemented by the examination of related constructs, including value creation; the roles, resources and processes involved; and the industry specific characteristics influencing customer experiences. The motivations for the study spawned from the researcher’s involvement and interest in customer-facing, consultative solution sales in the B2B software industry. To serve the purpose of the study, a literature review was conducted outlining prevalent literature and research into inherent concepts related to the customer experience. The resulting conceptual framework served as a platform for the empirical research. The empirical portion of the study was designed and conducted to examine the customer’s perspectives of the factors that influence their experience. The data collection was performed through a series of six semi-structured theme interviews with purposefully selected participants representing large multi-national corporations from a variety of industries. The findings were well representative of the proposed conceptual framework and provide insights into the contextual, perceived importance of factors influencing the customer experience in the engagements and relationships within the B2B software industry. The findings were thematically synthesized into nine categories reflecting the factors influencing the customer experience formation. These findings highlight the importance of the supplier’s role as the driving force throughout the engagement, while giving emphasis to the personal relationships and trust among the representatives of both parties. While the study mostly focuses on the dyadic nature of the relationship, the importance of value networks is also evident. With the scale and extent of the customer experience concept, it remains a fertile platform for further academic research and this study provides an outlook into the constructs available for further examination.